Chapter 9 Mitochondria Structure and Position in the Local Control of Calcium Signals in Smooth Muscle Cells - McCarron, John G. (Methods in Signal Transduction Series, 2019)
Features of Ca2+ signals including the amplitude, duration, frequency and location are encoded by various physiological stimuli. These features of the signals are decoded by cells to selectively activate smooth muscle functions that include contraction and proliferation [1-3]. Central, therefore, to an appreciation of how smooth muscle is controlled is an understanding of the regulation of Ca2+.